2014
DOI: 10.3758/s13414-014-0692-5
|View full text |Cite
|
Sign up to set email alerts
|

Size (mostly) doesn’t matter: the role of set size in object substitution masking

Abstract: Conscious detection and discrimination of a visual target stimulus can be prevented by the presentation a spatially non-overlapping, but temporally trailing, visual masking stimulus. This phenomenon, known as object substitution masking (OSM), has long been associated with spatial attention, with diffuse attention seemingly being key for the effect to be observed.Recently, this hypothesis has been questioned. We sought to provide a definitive test of the involvement of spatial attention in OSM using an eightal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 25 publications
2
47
1
Order By: Relevance
“…This finding has been recently replicated by using an eight-alternative forced-choice task (Filmer, Mattingley, & Dux, 2014), providing further evidence against the attention account of object-substitution theory. Pilling et al (2014) also employed a spatial cue to directly control spatial attention, and also reported no interaction.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…This finding has been recently replicated by using an eight-alternative forced-choice task (Filmer, Mattingley, & Dux, 2014), providing further evidence against the attention account of object-substitution theory. Pilling et al (2014) also employed a spatial cue to directly control spatial attention, and also reported no interaction.…”
Section: Introductionmentioning
confidence: 63%
“…Other studies provided empirical evidence for maskingattention interactions in metacontrast masking (Ramachandran & Cobb, 1995;Shelley-Tremblay & Mack, 1999;Tata, 2002), raising the possibility that these interactions could be an essential component of all masking types. However, recent studies, using the common-onset masking paradigm, showed that the interaction between masking and attention was an artifact of ceiling/floor effects and provided evidence against the p r e d i c t i o n o f t h e o b j e c t s u b s t i t u t i o n m o d e l (Argyropoulos et al, 2013;Filmer et al, 2014Filmer et al, , 2015Pilling et al, 2014). A goal of our study was to examine whether the interaction between attention and masking in metacontrast could also be a result of floor/ceiling effects.…”
Section: Discussionmentioning
confidence: 99%
“…4 Accuracy to identify the target, as a function of spatial frequency, set size, and hand proximity in Experiment 2. Error bars depict standard errors, corrected for within-subjects designs (Cousineau, 2005). object-substitution masking is not modulated by attention (Argyropoulos, Gellatly, Pilling, & Carter, 2013;Filmer, Mattingley, & Dux, 2014). Similarly, Kelly and Brockmole (2014) found an impairment in visual memory for color content in near-hand space when the requirement was to encode six items into memory.…”
Section: Discussionmentioning
confidence: 99%
“…While, as flagged earlier, the presence of simultaneous distractors is not a necessary condition for OSM, and there have been absences of interactions between masking and set-size in OSM reported when the items are widely spaced (Argyropoulos et al, 2013;Filmer et al, 2014), when the distractors are sufficiently close to the target to induce crowding, then an interaction between masking magnitude and the number of distractors is obtained (Camp, Pilling, Argyropoulos, & Gellatly, 2015). This interaction between crowding and OSM suggests that there may be at least some overlap in mechanisms; otherwise purely additive effects would be expected.…”
mentioning
confidence: 99%
“…Historically, target-like distractors have been presented in addition to the target (which appeared and disappeared simultaneously with the target). However, recent evidence indicates that the presence of distractors is not necessary to obtain masking (Argyropoulos, Gellatly, Pilling, & Carter, 2013;Filmer, Mattingley, & Dux, 2014Pilling, Gellatly, Argyropoulos, & Skarratt, 2014). OSM clearly reflects a failure to register the target as an enduring object for conscious perception.…”
mentioning
confidence: 99%